Bacterial Community and Spoilage Profiles Shift in Response to Packaging in Yellow-Feather Broiler, a Highly Popular Meat in Asia - Wang, Huhu; Zhang, Xinxiao; Wang, Guangyu; Jia, Kun; Xu, Xinglian; Zhou, Guanghong (Frontiers in Microbiology, 2017)
The consumption of yellow-feathered broiler has been advocated for purchasing with chilled meat rather than live broilers in Asia due to the outbreaks of animal influenza. Here, the microbial community of chilled yellow-feathered broiler response to modified-atmospheres packaging (MAP, 80% CO2 / 20% N2) and penetrated-air packaging (PAP, air-filling) during storage was revealed by a combination of whole-metagenome shotgun (WMS) sequencing and traditional isolation methods, and the volatile organic compounds and proteolytic activity of representative dominant isolates were also accessed. The results revealed that MAP prolonged shelf life from 4 days to 8 days compared to PAP, when the numbers of total viable counts and lactic acid bacteria reached more than 7 log CFU/g. Aeromonas, Acinetobacter, Escherichia and Streptococcus occupied the bacteria communities in initial broiler carcasses. MAP dramatically increased the bacteria diversity during storage compared to PAP. Clear shifts of the dominant bacteria species were obviously observed, with the top genera of Aeromonas, Lactococcus, Serratia and Shewanella in MAP, whereas the microbial communities in PAP were largely dominated by Pseudomonas. The isolates of Pseudomonas from PAP carcasses and Aeromonas from MAP carcasses displayed strong proteolytic activities. Meanwhile, the principal component analysis (PCA) based on the volatile organic compounds indicated that the metabolic profiles greatly varied between each treatment, and no link between the natural odor of spoilage meat in situ and the volatile odor of the dominant isolates incubated in standard culture was found. These data could lead to new insights into the bacteria communities of yellow-feathered broiler meat during storage and would benefit the development of novel preservative approaches.